Thermodynamic Parameters, NBO Analysis, HOMO-LUMO and MEP Analysis of (5R)-2-Methyl-5-[(2S)-6-Methyl-5-Hepten-2-yl]-1,3-Cyclohexadiene Using HF and DFT Calculations - Mahin Ahmadianarog (Journal of Global Pharma Technology, 2017)
Ginger plant is a well-known spice and flavoring agent which has also been used in traditional medicine in many countries. Ginger contains essential oils including Gingerol and Zingiberene. Zingiberene is a monocyclic sesquiterpene that gives a distinctive flavor to ginger. The quantum theoretical calculations for Zingiberene were performed by using HF/6-31G, HF/6-31G(d), B3LYP/6-31G, B3PW91/6-31G and BLYP/6-31G level. The EHOMO-1, ELUMO ELUMO+1, HOMO-LUMO energy gap (Eg), and dipole moment (µD) obtained for Zingiberene. According to the calculated HOMO and LUMO energies, molecular properties such as Ionisation Potential (I), Electron affinity (A), chemical hardness (η), electronic chemical potential (μ) and electrophilicity (ω) obtained and also show that charge transfer occurs in Zingiberene. The frontier molecular orbitals (FMOs) and molecular electrostatic potentials (MEPs), the chemical shielding tensors (CS), thermodynamic parameters, natural charge and NBO analysis were investigated for title structure by theoretical calculations. Keywords: Ginger, Zingiberene, Energy gap, Natural charge, NBO analysis.